2021
DOI: 10.3390/electronics10141626
|View full text |Cite
|
Sign up to set email alerts
|

Managing SARS-CoV-2 Testing in Schools with an Artificial Intelligence Model and Application Developed by Simulation Data

Abstract: Research on SARS-CoV-2 and its social implications have become a major focus to interdisciplinary teams worldwide. As interest in more direct solutions, such as mass testing and vaccination grows, several studies appear to be dedicated to the operationalization of those solutions, leveraging both traditional and new methodologies, and, increasingly, the combination of both. This research examines the challenges anticipated for preventative testing of SARS-CoV-2 in schools and proposes an artificial intelligenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…The study also showed good use of non‐Markovian models to better capture the spreading dynamics (Yang et al, 2020 ). In a school environment setting, a study proposed an artificial intelligence (AI)‐powered ABM (Valtchev et al, 2021 ) to examine the challenges anticipated for preventative testing of COVID‐19. Two studies combined machine‐learning algorithms with ABM to model the COVID‐19 transmission (Ozik et al, 2021 ) and calculated the effects of the COVID‐19 pandemic on the banking system and the real economy (Polyzos et al, 2021 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The study also showed good use of non‐Markovian models to better capture the spreading dynamics (Yang et al, 2020 ). In a school environment setting, a study proposed an artificial intelligence (AI)‐powered ABM (Valtchev et al, 2021 ) to examine the challenges anticipated for preventative testing of COVID‐19. Two studies combined machine‐learning algorithms with ABM to model the COVID‐19 transmission (Ozik et al, 2021 ) and calculated the effects of the COVID‐19 pandemic on the banking system and the real economy (Polyzos et al, 2021 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There are several advantages of using AI to fight against pathogens such as viruses and bacteria that cause a complex reaction in the host [32]. DNN can accelerate the discovery of valuable vaccines or drugs to prevent pandemics and facilitate the diagnosis of diseases [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…From the above, it can be seen that AI is effectively used in various aspects of COVID-19 countermeasures. Due to space limitations, we were unable to describe them in this review, but notable contributions have also been made through the use of distributed artificial intelligence and agent-based models [138][139][140]. We note that, from the perspective of preventing infectious diseases, it is necessary to reduce human contact and unnecessary human flow, which is why information and communication technology in social life is advancing worldwide [141][142][143].…”
Section: Discussionmentioning
confidence: 99%